ナンキョク ロケット ニヨル プラズマ ハドウ ノ カンソク ケイカク - 大家, 寛; オオヤ, ヒロシ; OYA, Hiroshi (国立極地研究所, 1975)
P(論文) The plasma wave observations in the polar ionosphere consist of two categories; the first is for the emission due to the particle precipitation and the second is for the emissions that are thought to be generated in the magnetosphere as a result of the conversion of the plasma waves into the electromagnetic waves. The first kind of the observation is important for the confirmation of the anomalous resistivity that is included in the nonlinear beam instability. The second kind of observation is important for the analyses of the wave particle interaction processes in the deep magnetosphere. The over all feature of the wave-particle interaction processes in the polar ionospheric plasma should be clarified by the rocket experiments that are coordinated with the instruments for the measurements of the waves and particles. The large scale co-ordination of the observations that are organized by the rocket measurements, ground observation and the satellite observations, is required to achieve these projects. departmental bulletin paper